PENERAPAN MEDIA AUDIO VISUAL DALAM PENINGKATAN PEMAHAMAN HAJI DAN UMRAH - Endang Sugiyanti (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2020)
Learning design must be arranged systematically. In the Learning process, the teacher plays an important role in determining the success or failure of learning achievement. The selection of appropriate learning media is something that teachers need to pay attention to with the application of Audio Visual media to improve students' understanding in following the learning process on the subject of Jurisprudence and pilgrimage material. The formulation of the problem is: How is the application of Audio Visual media in increasing the activeness and learning outcomes of students in the subject of Jurisprudence and Umrah in MTs Negeri 28 Jakarta, in collecting data the author uses tests, observations and student responses. The results of the application of audio-visual media answered from the formulation of the problem where the application of audio-visual media on the learning of the material of hajj and umrah pilgrimage has achieved success. Student learning outcomes in the fiqh learning of Hajj and Umrah material has reached its completeness with an average value of 88.09 with a percentage of 95.6% clearly visible improvement in learning outcomes after using audio-visual media has improved better.